Analisis Kesiapan Implementasi RME Rawat Inap dengan DOQ-IT di Rumah Sakit Port Medical Center - Novia Nurhikmah Sari; Daniel Happy Putra; Noor Yulia; Dina Sonia (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The development of the health care industry, one of which is hospitals, and the enactment of Permenkes 24 of 2022 concerning RME, which requires all health facilities to implement RME. This study aims to determine the readiness of inpatient RME implementation at Port Medical Center Hospital which is in the process of transmitting conventional medical records to RME. This study aims to determine the readiness of health facilities in implementing RME. Involving 100 respondents involving; Decision Making Team, Doctors, Outpatient and Emergency Room Units, Inpatient and ICU Units, Central Opname, Radiology Unit, Unit, Laboratory, Nutrition Unit, Physiotherapy Unit, Pharmacy Unit, and Information Systems Technology Unit. The research time was conducted October 2022 - June 2023. The data collection technique used a questionnaire. The results of the study, Readiness for Implementation of Inpatient EMR at Port Medical Center Hospital is in category II, which is quite ready with aspects of organizational alignment at a score of 24.91 and aspects of organizational capacity at a score of 44.24 in the category of quite ready. Readiness in the implementation of RME needs to be improved in terms of work culture regarding discussions of the framework, decision-making teams, discussions regarding accountants, and infrastructure improvements.